Penerapan Nilai-Nilai Islam Dalam Praktik Manajemen Berbasis Islam (Studi Kasus Hotel Haz Syariah Semarang) - Yogasara, Fadli Ahmad; Mas’ud, Fuad (Diponegoro Journal of Islamic Economics and Business, 2021)
Demand on halal toursim is increase recently, especially in Indonesia that is in the 2nd place based on GMTI 2019. Furthermore, application of tourism also related to business management. While at the same time Indonesia itself is one of the largest Muslim country in the world, this leads more demand on the application of Islamic-based management which is the management that comprehensively practices the value of Islam that based on the al-Quran and as-Sunnah.  One of that practical aspect in Isamic-based management that can be seen  in tourism is hotel sector. This study try to explore the application of Islamic values in Islamic based management in Haz Syariah hotel, Semarang. This study is a qualitative approach, with a single instrumental case study as a method where only focus on one particular issue. The reason for choosing this method is to discussed more specifically about the evaluation of Islamic values in the practice of Islamic-based management at the Haz Syariah Hotel Semarang. The results of the study show that leadership and staff have a good understanding of the application of Islamic values in business management. These values are trust and responsibility, help, fairness, ihsan, halallan thayyiban, and deliberation. However, the values that are not included in this study is about honesty, reading and a sense of consideration.